(untitled) (GESTIÓN Y TENDENCIAS, 2019)
Few people today deny the significant economic, social, and environmental effects intimately bound up with the phenomenon of consumption —effects that also concern business practice. The future taking shape before us demands that business innovation be repositioned in a context of greater social engagement. And it is urgent.